FACTORS AFFECTING NEWBORN WEIGHT - Eka Rati Astuti; Harlen Yunita (POLTEKKES KEMENKES JAYAPURA, 2022)
The nutritional status and health of the baby can be described, one of which is the weight at birth. In addition, the incidence that occurs in infants during gestation and its association with various factors, including parity, maternal age, hemoglobin level, gestational interval, pregnancy examination, upper arm circumference, socioeconomic environment, and disease during pregnancy. This study aims to analyze the factors that affect newborn weight in Kedurang District, South Bengkulu Regency, in 2020. This study used an analytical observational method with a retrospective cohort study design. The population used is 57 people, namely pregnant women with data on hemoglobin levels in the third trimester and delivery data in Kedurang District. All population members are used as research subjects (total sampling). Data analysis used chi-square and linear regression. There were 57 respondents; 80.7% were of no-risk age, 45.6% had low education, 56.2% were multigravida, and 54.8% had anemia. As many as 28.1% of infants born with low birth weight have the most significant risk factors anemia (54.8%), primigravida (40.5%), primary education (28.6%), and age at risk (19.1% ). The results showed an influence between the mother's age and the newborn's weight (p=0.001) with an OR value of 1.1. In addition, there is an effect between education and newborn weight (p = 0.009) with an OR value of 13. There is also an effect between parity and newborn weight (p = 0.003) with an OR value of 11.4. In addition, there was an effect between the mother's Hb value and the newborn's weight (p=0.004), with an OR value of 10.6. Based on the OR value, sequentially, the factors that affect the newborn's weight are education, parity, Hb value, and maternal age. Keywords: Anemia, Low birth weight babies, Hb level, Parity, Mother's age